Strategic ionomer design for high performing fuel cells with open cathode. (8th January 2022) - Sagar, Anand; Chugh, Sachin; Sharma, Alok; Kjeang, Erik
Abstract: The performance of open-cathode fuel cell systems is limited by deficient humidification and thermal gradients within the individual cells. This work investigates ionomer design strategies to passively control hydration and thereby overcome the inherent performance limitations of such systems. An experimentally validated three-dimensional computational model is used to analyze the effect of a critical ionomer property, namely the water sorption/desorption rate constant at three levels, for cell performance and spatially resolved temperature and water activity. The current density at 0.6 V is found to increase remarkably by 130% by reducing the water sorption/desorption rate constant from 10 s −1 to 0.1 s −1 under ambient air at 40 °C and 40% relative humidity. This is accomplished through enhanced water retention and membrane hydration at elevated temperature. Highlights: The effect of ionomer properties on open-cathode fuel cell performance is simulated. Lower ionomer water sorption/desorption rate constant boosts cell performance. Membrane drying and slow kinetics are mitigated through strategic ionomer design.